2008
DOI: 10.1080/01650420701880974
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns in the aquatic insect community of a high altitude Andean stream (Mendoza, Argentina)

Abstract: Benthic invertebrate communities have been poorly studied in Andean streams apart from the Patagonian region. The primary objective of this work was to analyse the faunal composition at three different altitudes and to observe whether there were differences in aquatic insect community structure at spatial and temporal scales. Physicochemical variables were measured on a monthly basis. Sixteen families were found, the most frequent and abundant taxa being Massartellopsis (Ephemeroptera), Andesiops (Ephemeropter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
2
16
0
4
Order By: Relevance
“…Indeed, species richness in arid regions has been found to be notably low relative to areas with higher precipitation (Wright & Burgin 2010). Similar research on different aquatic environments in the Mendoza province has also reported low taxonomic richness (Scheibler 2007, Scheibler & Debandi 2008, Scheibler & Ciocco 2011.…”
Section: Prevalence Of Chironomids and Environmental Variablesmentioning
confidence: 73%
See 2 more Smart Citations
“…Indeed, species richness in arid regions has been found to be notably low relative to areas with higher precipitation (Wright & Burgin 2010). Similar research on different aquatic environments in the Mendoza province has also reported low taxonomic richness (Scheibler 2007, Scheibler & Debandi 2008, Scheibler & Ciocco 2011.…”
Section: Prevalence Of Chironomids and Environmental Variablesmentioning
confidence: 73%
“…However, in glacial stream ecosystems with harsh conditions within different regions across Europe, the species richness of chironomid assemblages was found to be much higher (for example, 39 genera recorded; Lods-Crozet et al 2001) than in the Andean river of the present study, with only 11 genera recorded. We attribute these low diversities to the aridity of the sampling area, as has been demonstrated in studies of other similar high-altitude lotic systems (Scheibler & Debandi 2008, 2014. Table 1 Site Sampling Conductivity Ca …”
Section: Databases 1 and 2: Chironomid Community Diversitymentioning
confidence: 84%
See 1 more Smart Citation
“…However, in several mountain streams there is a higher contribution of the taxonomic richness of the orders Plecoptera, Ephemeroptera, and Trichoptera to the benthic community (Maiolini and Lencioni, 2001;Figueroa et al, 2003;Miserendino and Pizzolon, 2003), and overall higher invertebrate richness (Finn and Poff, 2005;Bogan and Lytle, 2007;Brown et al, 2007). Nevertheless, in the Uspallata stream, a tributary of the Mendoza River, it was found that Diptera and Ephemeroptera compose 60% of the benthic community, with low diversity of the orders Plecoptera, Trichoptera, and Coleoptera (Scheibler and Debandi, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that longitudinal studies contribute data on species distribution ranges and that turnover of macroinvertebrate assemblages Finn and Poff, 2005) in environmental gradients (Knispel and Castella, 2003) as well as description of these patterns are important contributions to ecological studies (Jacobsen, 2004). Furthermore, seasonal studies provide information about the variability of physical-chemical conditions experienced by mountain streams (Füreder, 1999;Knispel and Castella, 2003), which affects macroinvertebrate densities (Scheibler and Debandi, 2008). Mountain streams are significant systems for studying spatial biological processes (Finn and Poff, 2005) and are environments likely to be more affected by global climate change and human impact than rivers at lower altitudes (Burgherr and Ward, 2001;Finn and Poff, 2005).…”
Section: Introductionmentioning
confidence: 99%